Project manager performance improvement for design and build construction state building - Kusumawati, Jujuk (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
The Design and Build (D&B) method has become a dominant approach in Indonesian government construction projects due to its potential to accelerate project timelines by integrating design and implementation. However, significant delays persist—especially in Jakarta indicating that technical improvements alone are insufficient. This study investigates how managerial behavior and work culture influence the timeliness of government D&B construction projects. Using a quantitative approach, surveys were conducted among project managers, construction consultants, and procurement officials involved in D&B projects in Jakarta between 2015 and 2018. Key variables examined include leadership style, decision-making agility, work ethic, communication effectiveness, problem-solving ability, and technical competence. Regression analysis revealed that leadership and work ethic positively affect timely completion. Surprisingly, communication effectiveness and agile decision-making were associated with delays, likely due to bureaucratic complexity and unstable project environments. Technical and problem-solving skills proved insufficient without strong behavioral support. The findings underscore the importance of behavioral competencies particularly leadership and discipline in project performance. The study also noted inconsistencies in instrument reliability, suggesting refinement for future use. Recommendations include revising recruitment standards to emphasize behavioral attributes and enhancing methodological rigor in similar research. A shift in focus from purely technical to integrated behavioral competencies is essential for improving public sector project outcomes.